Using Neural Networks to Classify COVID-19 Death Rates Cases in Iraq - غافل, . منى (The Gulf Economist, 2024)
Neural networks were used in the current study for the classification of Covid-19 death rates in Iraq at four different stages. This was led to a classification accuracy of 96.7% for high-severity deaths, and 95.5% for low-severity deaths. The percentage of correct classification of high-severity deaths, it was 86% at 10%, and 91% for low-severity deaths. Finally, the network accuracy rate reached 93.9%. This research paper shows the effectiveness of neural networks in understanding and classifying cases of Covid-19 deaths and studying the impact of the pandemic in Iraq.